The EU competition investigation into Gazprom’s Sales to Central and Eastern Europe: a detailed analysis of the commitments and the way forward - Stern, J; Yafimava, K (Oxford Institute for Energy Studies, 2017)
A detailed analysis by Jonathan Stern and Katja Yafimava of Gazprom’s March 2017 competition commitments in respect of gas sales to Central and Eastern Europe, concludes that the concerns expressed by DG COMP in respect of territorial restrictions, pricing, and infrastructure issues have been addressed, both in form and in substance. Acceptance of these commitments would provide insurance against future abuse by Gazprom of its dominant position in these countries. Most importantly, Gazprom has henceforth agreed to charge average weighted import border prices and/or prices at relevant generally accepted liquid hubs in Continental Europe instead of alternative fuel (oil-linked) prices. This means that if the commitments are accepted, buyers in these countries will be able to buy Russian gas at hub prices before interconnections have been established with these hubs (potentially up to three years hence). The acceptance by Gazprom of competitive, defined as liquid hub, prices has much wider significance, as it signals the end of alternative fuel pricing for gas in EU countries. DG COMPs market test of the commitments elicited a generally positive response with the exception of Poland’s PGNiG which expressed deep dissatisfaction on virtually all issues, in particular the lack of any fine or obligation for Gazprom to pay compensation for its past behaviour. The study suggests that the most likely outcome is the acceptance by DG COMP of the commitments (with minor amendments) and closure of the case with a settlement. Should some member states, specifically Poland, attempt to derail the settlement, causing the case to be referred to the EU Court of Justice (CJEU), the commitments are still likely to be implemented but legal proceedings could drag on for several more years.